Perception of Financial Statement Preparation and Efforts to Increase Accountability Awareness - Suprapti, Suprapti; Farliana, Nina; Utami, Evita Septiana Tyas (Department of Economics Education, Faculty of Economics, Universitas Negeri Semarang, 2021)
This study aimed to analyze the researcher's perception of research financial responsibility system, what factors make researchers feel difficulties and objections in conducting financial reports, and how to develop strategies to improve literacy of researchers' understanding to prepare financial reports. This type of research was descriptive qualitative. The research location is at Universitas Negeri Semarang. The total informants were 33 researchers who were taken by the technique of purposive sampling. Methods of data collection used interviews, observation and documentation. The data analysis technique used data reduction, data presentation and conclusion drawing. The results of study indicated that the preparation of accountability reports was very important in research, because it helped in monitoring the use of research funds, controlling expenditures, and making the use of research funds more effective and efficient. The obstacles that researchers face in preparing financial statements were the limited time of researchers, some expenses that could not be reported in the accountability system, as well as various regulatory changes. Efforts to overcome existing obstacles by reporting and consulting with related parties, namely the finance department, involved a team that was competent in finance and asked for help from related administrative staff and improved the financial literacy of researchers.